Analysis on the electric vehicle with a hybrid storage system and the use of Superconducting magnetic energy storage (SMES). (November 2021) - Molina-Ibáñez, Enrique-Luis; Rosales-Asensio, Enrique; Pérez-Molina, Clara; Pérez, Francisco Mur; Colmenar-Santos, Antonio
Abstract: Given the current load and power density limitations in electric vehicle (EV) storage systems, it is necessary to study hybrid and control systems in order to optimize their performance and present themselves as a real alternative to internal combustion engine (ICE) vehicles. This implies the development of legislation and specific regulations that enable the research and development of these storage and management systems for hybrid systems. The research presented here aims to analyze the implementation of the SMES (Superconducting Magnetic Energy Storage) energy storage system for the future of electric vehicles. To do this, the need for a hybrid storage system has been taken into account, with several regulatory options, such as the reduction of rates or the promotion of private investments, which allow the technological development of EVs. What is sought is to achieve the market share proposed by the different countries to reduce Greenhouse Gases (GHG), according to their objectives. This approach must be taken from the legislative and regulatory perspective, specific to EVs and charging points, of several countries or regions with different cultures, management models and implementation potential, such as the United States of America (USA), Europe and China. This analysis is associated with the economic study of costs that this storage system may involve in the implementation of EVs to replace ICE vehicles, resulting in possible economic benefits as well as the environmental benefits of the use of EVs. In this analysis, the current high cost of using a hybrid system of these characteristics can be observed with the comparison of three EVs, as well as current data on GHG emissions produced by transport. All this leads to a series of advantages and disadvantages that must be taken into account in order to achieve the objectives that countries have in the coming decades of EV diffusion.